2002
DOI: 10.1007/s11881-002-0015-8
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of assistive reading software for students with attention disorders

Abstract: This study investigated how assistive reading software affected the reading performance of a group of 20 post-secondary students who had a primary diagnosis of attention disorder. These students used assistive reading software for most of a semester to read assignments for an English class and in testing sessions in which comparisons were made between normal, unassisted reading, and reading assisted by the soft-243 244 THEORY-BASED PRACTICE ware. This software provides a synchronized visual and auditory presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 14 publications
4
59
1
1
Order By: Relevance
“…Other technologies have been developed to self-manage ADHD-related difficulties in children and YP that can be used independently of a therapist which, therefore, reduces the reliance on services. These include a handheld organisation device [30], a device to self-monitor ADHD symptoms [31], computer software to improve reading speed [32], and computer games that focus on mathematical ability [33] and the promotion of behavoural learning and organisation [34]. Although these studies report that technology has the potential to self-manage ADHD-related difficulties in children and YP, little is known about the level of evidence for these technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Other technologies have been developed to self-manage ADHD-related difficulties in children and YP that can be used independently of a therapist which, therefore, reduces the reliance on services. These include a handheld organisation device [30], a device to self-monitor ADHD symptoms [31], computer software to improve reading speed [32], and computer games that focus on mathematical ability [33] and the promotion of behavoural learning and organisation [34]. Although these studies report that technology has the potential to self-manage ADHD-related difficulties in children and YP, little is known about the level of evidence for these technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Computer use in school provides a novel alternative to traditional instruction that may capture the attention of students with ADHD. In addition, computer use can also lead to significant improvement in active engagement time, on-task behaviour, improvement in attention (5,(14)(15)(16) and educational performance in reading (17)(18) and maths (19)(20), thus making these findings critical for students with ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…Computer use by students with ADHD can promote motivation for learning (13), active responding and attention (14) and prevent off-task behaviour during educational activities (5,15,16). It has been clearly suggested that computer use in school by students with ADHD can support oral reading fluency (17) and increase in periods of sustained reading and decrease in distractions (18). In addition, computer use may also support educational performance in mathematics achievement for students with ADHD, compared with written seatwork conditions, both in general educational settings (19) and special educational settings (20).…”
Section: Introductionmentioning
confidence: 99%
“…Only the study by Hecker, Burns, Elkind, Elkind and Katz (2002) was designed to determine the potential benefits of the use of modern technologies in the reading performance of post-secondary students with a diagnosis of ADHD. The majority of the participants were taking psychostimulant medication, and 25% suffered from RD.…”
Section: Assessment and Intervention In Adhd And Rdmentioning
confidence: 99%